Ottawa materials, Indian manuscripts, 1661-1879 - Unknown (1699)
Materials prepared by French Sulpician missionaries in New France in the French and Ottawa [or Odawa] languages. Includes a petit catechisme, a literal, page-by-page translation into Ottawa of the "Catechisme des fetes principales de l'annee publie a Chartres par Etienne Massot le Jeune en 1683"; and "Racines de la langue 8ta8aise et algonquine," A to S only. The last 56 pages of the latter contain "Instructions sur les exhortations relatives aux commandements" while the cover reads "Instruction sur les symboles." Originals in Seminaire de Montreal, les Pretres de Saint-Sulpice.